Choc Culturel Dans Le Film Ã¢â‚¬Å“WaÃ¢â‚¬â„¢alaikumussalam ParisÃ¢â‚¬Â De Benni Setiawan - Fitriani, Nur Azizah; Syaefudin, Mohamad (Didacticofrancia: Journal Didactique du FLE, 2021)
Abstract Le objectifs de cette recherche est d'identifier les problÃƒÂ¨mes culturels entre l'IndonÃƒÂ©sie et la France dans le film Ã‚Â«Wa'alaikumussalam ParisÃ‚Â» et de connaÃƒÂ®tre les ÃƒÂ©tapes du choc culturel dans le film Ã‚Â«Wa'alaikumussalam ParisÃ‚Â» et comment les surmonter. Cette recherche est une ÃƒÂ©tude descriptive qualitative. Cette ÃƒÂ©tude utilise des donnÃƒÂ©es sous forme de dialogues / monologues et de scÃƒÂ¨nes du film Ã‚Â«Wa'alaikumussalam ParisÃ‚Â». Les rÃƒÂ©sultats obtenus sont qu'il y a plusieurs problÃƒÂ¨mes culturels entre l'IndonÃƒÂ©sie et la France dans le film Ã‚Â«Wa'alaikumussalam ParisÃ‚Â», ÃƒÂ  savoir, 1) des diffÃƒÂ©rences dans la nourriture, 2) des diffÃƒÂ©rences dans la faÃƒÂ§on d'interagir, et 3) des diffÃƒÂ©rences dans la culture familiale. Ensuite, il y a quatre phases de choc culturel dans le film Ã‚Â«Wa'alaikumussalam ParisÃ‚Â». Phase lune de miel se produit quand Itje heureux d'ÃƒÂªtre amenÃƒÂ© en France pour y vivre. La phase de crise ou de maladie survient lorsque Itje arrive ÃƒÂ  sa nouvelle rÃƒÂ©sidence, n'est pas habituÃƒÂ© au pain, aux limitations du langage, d'hostilitÃƒÂ©, compare et idÃƒÂ©alise le lieu d'origine. La phase d'adaptation a eu lieu lorsquÃ¢â‚¬â„¢Itje a commencÃƒÂ© ÃƒÂ  suivre la culture autochtone. La phase de maÃƒÂ®trise a eu lieu quand Itje cÃƒÂ©lÃƒÂ¨vre la fÃƒÂªte des rÃƒÂ©coltes. Quant ÃƒÂ  la faÃƒÂ§on de surmonter le choc culturel dÃƒÂ©peint dans le film Ã‚Â«Wa'alaikumussalam ParisÃ‚Â», il y a un soutien social des personnes les plus proches, ClÃƒÂ©ment et Dadang. Abstract The purpose of this research is to identify cultural problems between Indonesia and France in the film "Wa'alaikumussalam Paris" and to know the stages of cultural shock in the film "Wa'alaikumussalam Paris" and how to overcome them. This research is a qualitative descriptive study. This study uses data in the form of dialogues / monologues and scenes in the film "Wa'alaikumussalam Paris". The results obtained are that there are several cultural problems between Indonesia and France in the film "Wa'alaikumussalam Paris", namely, 1) differences in food, 2) differences in how to interact, and 3) differences in family culture. Then there are four phases of cultural shock in the film "Wa'alaikumussalam Paris". Phase honeymoon occurs when Itje happy to be brought him to France to live there. The crisis or sickness phase occurs when Itje arrives at his new residence, is not used to bread, language limitations, hostility, and compares and idealizes the place of origin. The adaptation phase occurred when Itje began to follow indigenous. The mastery phase occurred when Itje celebrates the harvest festival. As for how to overcome the cultural shock depicted in the film Ã¢â‚¬Å“Wa'alaikumussalam ParisÃ¢â‚¬Â, there is social support from the closest people, namely from ClÃƒÂ©ment and Dadang